THE IMPLEMENTATION OF POP UP NOTIFICATION ON ONLINE QUEUE SYSTEM IN HEALTH CLINIC, USING WEBSITE AND ANDROID PLATFORM - Alfin Siddik Amrullah; Muhammad Aziz Fatchur Rachman (Universitas Islam Sultan Agung, 2020)
Queuing is a tedious activity and can spend a lot of time for some people, especially if it is a queue at a health clinic. The usual queue is the prospective patient (the person who is sick), have to undergo a queue process so long before can get health care. To facilitate the process of queuing at the health clinic and solve problems in the conventional queuing system, the author designed an Online Queue System at a health clinic using Waterfall system development method. The output of this queue system is divided into three components; namely